2005
DOI: 10.1007/s10562-005-7154-6
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrogenation of 2-butyne-1,4-diol over a Carbon-supported Palladium Catalyst

Abstract: The hydrogenation of 2-butyne-1,4-diol in propan-2-ol over a carbon-supported palladium catalyst has been investigated in a batch reactor. At low conversions complete selectivity to cis-but-2-ene-1,4-diol is observed. However, further hydrogenation leads to a wide variety of products, most notably 2-isopropoxy-tetrahydrofuran and butane, neither of which have previously been associated with this reaction system. The former is thought to occur as a result of a surface-mediated process, involving the insertion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Depending on the catalyst used, the reaction solvent, and the nature of the support material, the ratio between the cis -BED and the γ-HALD may vary over a wide range. It has been shown that, using basic supports or base additives in the liquid phase, the double bond isomerization into γ-HALD route can be completely suppressed resulting in the exclusive formation of cis -BED. ,, In the second Stage B, shown in Scheme , the dominant species on the catalyst surface are the two alkene complexes, 2 and 3 , both generating BAD, trans -BED, and γ-HALD. The observed consumption of cis -BED in this kinetic stage and the accumulation of the trans -BED shows the preferential adsorption of the cis -enol over the trans -form when both compete for the same active sites on the catalyst surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the catalyst used, the reaction solvent, and the nature of the support material, the ratio between the cis -BED and the γ-HALD may vary over a wide range. It has been shown that, using basic supports or base additives in the liquid phase, the double bond isomerization into γ-HALD route can be completely suppressed resulting in the exclusive formation of cis -BED. ,, In the second Stage B, shown in Scheme , the dominant species on the catalyst surface are the two alkene complexes, 2 and 3 , both generating BAD, trans -BED, and γ-HALD. The observed consumption of cis -BED in this kinetic stage and the accumulation of the trans -BED shows the preferential adsorption of the cis -enol over the trans -form when both compete for the same active sites on the catalyst surface.…”
Section: Resultsmentioning
confidence: 99%
“…In a subsequent work by Telkar et al on the hydrogenation of BYD over a series of supported palladium catalysts, the formation of n -butanal was attributed to an alternative reaction pathway, described by reactions a–d–h. According to this, the n -butanal is formed through hydrogenolysis of the 4-hydroxybutanal (γ-HALD) which is itself generated from the cis- BED intermediate . The same reaction set was later expanded in the work by Musolino et al reporting on the formation of the cyclic hemiacetal 2-hydroxytetrahydrofuran (HTHF) through reaction sequence a–d–f.…”
Section: Introductionmentioning
confidence: 99%
“…Samples were analyzed by gas chromatography with a flame ionization detector using a 456 SCION GC (DB-WAX 52 column, length 32 m, inner diameter = 0.3 mm) and helium (30 mL/min) as a carrier gas, according to previously reported analysis methods [30][31][32][33]. Reaction samples were injected into the GC and analyzed under the following conditions: temperature detector was set at 518 K, injector temperature at 513 K, the initial oven temperature was 353 K and this was raised up to 493 K at a rate of 10 K/min.…”
Section: Hydrogenation Of 2-butyne-14-diolmentioning
confidence: 99%
“…Nickel‐based catalysts have attracted increased attention due to their relatively low cost and high intrinsic activities . It was already reported that Ni supported catalysts can be used with the desired catalytic properties (e. g. activity, selectivity, and stability) during the hydrogenation process, which is superior in comparison with the Raney nickel catalysts …”
Section: Introductionmentioning
confidence: 99%
“…Duncanson et al . showed that n‐butanal could be formed through hydrogenolysis of 4‐hydroxybutanal (γ‐HALD) which was generated from cis ‐BED intermediate . Musolino et al .…”
Section: Introductionmentioning
confidence: 99%